2022
DOI: 10.1177/17474930221136704
|View full text |Cite
|
Sign up to set email alerts
|

The Twitter factor: How does Twitter impact #Stroke journals and citation rates?

Abstract: BACKGROUND Twitter is a social media platform popularly used by health practitioners, a trend that has been followed by medical journals. The impact of Twitter in bibliometrics of stroke-related literature is yet to be determined. AIMS We aimed to qualitatively assess the usage of Twitter by stroke journals and study the relationship between Twitter activity and citation rates of stroke articles. METHODS We used Journal Citation Reports to identify stroke journals. We collected the 2021 Impact Factor (IF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
1
1
1
Order By: Relevance
“…The results of this study suggest that there is a relationship between a journal's Twitter activity and its SJR score. This is consistent with previous studies that have also found an association between Twitter activity and SJR, specifically with the number of followers [10,11,[14][15][16]. However, these studies only looked within one specialty, not across multiple specialties as in this analysis.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study suggest that there is a relationship between a journal's Twitter activity and its SJR score. This is consistent with previous studies that have also found an association between Twitter activity and SJR, specifically with the number of followers [10,11,[14][15][16]. However, these studies only looked within one specialty, not across multiple specialties as in this analysis.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, although social media is seen as a new tool in impact assessment in the literature, the findings of our study suggest otherwise. (12) In conclusion, although it is commonly thought that journals actively using social media have higher Impact Factors (IF) and that there is a strong relationship between the impact power and social media activity, our study has found no difference in average activity, number of shares, likes, comments, and RTs as IF increases. On the other hand, journals with high IF, even when making a similar number of posts and receiving a similar number of likes, comments, and RTs, tend to have more followers, a higher total number of shares, and a greater average number of views.…”
Section: Figure 6 Correlation Between If and Follower Count Over Six ...contrasting
confidence: 71%
“…There is some evidence that tweeted stroke articles may improve the citation rates of the article. [ 26 ] This is an area of future research and deserves further exploration.…”
Section: Discussionmentioning
confidence: 99%